Seismic Performance Evaluation Framework Considering Maximum and Residual Inter-Story Drift Ratios: Application to Non-Code Conforming Reinforced Concrete Buildings in Victoria, BC, Canada - Tesfamariam, Solomon; Goda, Katsuichiro (Frontiers in Built Environment, 2015)
This paper presents a seismic performance evaluation framework using two engineering demand parameters, i.e. maximum and residual inter-story drift ratios, and with consideration of mainshock-aftershock (MSAS) earthquake sequences. The evaluation is undertaken within a performance-based earthquake engineering framework in which seismic demand limits are defined with respect to the earthquake return period. A set of 2-, 4-, 8-, and 12-story non-ductile reinforced concrete buildings, located in Victoria, British Colombia, Canada, is considered as a case study. Using 50 mainshock and MSAS earthquake records (two horizontal components per record), incremental dynamic analysis is performed, and the joint probability distribution of maximum and residual inter-story drift ratios is modeled using a novel copula technique. The results are assessed both for collapse and non-collapse limit states. From the results, it can be shown that the collapse assessment of 4- to 12-story buildings is not sensitive to the consideration of MSAS seismic input, whereas for the 2-story building, a 13% difference in the median collapse capacity is caused by the MSAS. For unconditional probability of unsatisfactory seismic performance, which accounts for both collapse and non-collapse limit states, the life safety performance objective is achieved, but it fails to satisfy the collapse prevention performance objective. The results highlight the need for the consideration of seismic retrofitting for the non-ductile reinforced concrete structures.